Attitudes Towards LGBT Individuals After bostock v. Clayton County: Evidence From a Quasi Experiment. (December 2022) - Thompson, Jack
Do United States Supreme Court decisions on LGBT rights shape attitudes towards LGBT individuals among the mass public? In this paper, I conduct an empirical test of the effect of quasi-random exposure to the announcement of Bostock v. Clayton County—a landmark case which held that an employer who fires their employee because of their sexual orientation or gender identity violates Section VII of the 1964 Civil Rights Act—on favorability towards LGBT individuals. Relying on data from Phase 2 of the Democracy Fund/UCLA Nationscape survey, I find that quasi-random exposure to the announcement of Bostock engendered increases in favorability towards LGBT individuals among the wider American public. Subgroup analyses also indicate that the largest increases in favorability were among Democratic partisans and the religiously unaffiliated, while minimal changes in favorability were detected among those who are among the most likely to oppose LGBT rights, including Republicans and Evangelical Protestants. The findings speak to the validity of the legitimacy model and highlight the limitations of the backlash model in the post-Obergefell era of public opinion towards LGBT rights.